A política de assistência estudantil : estudo sobre condicionalidades - Silva, Juliana Barreto da (2016)
This thesis aims to analyze the design and application of the conditions in the context of Student Assistance Policy Federal Institutions of Public Higher Education. These institutions conditionalities are requirements counterparts for maintenance benefits offered by funds from the National Student Assistance Program and are configured generally in charge of academic performance and work. Failure to comply with the conditionalities usually implies sanctions ranging from suspension of benefits to the exclusion of student politics. Such actions not supported by the current national laws governing student assistance (Decree No. 7,234 / 2010), however, are maintained by the institutions. So, to put on the agenda the discussion of conditionalities broke what was constituted as a research problem: as the conditionalities have been designed and operationalized in the Student Assistance Policy Federal Institutions of Public Higher Education? The study was developed through a qualitative research, based on the critical dialectical method. To support the discussion, the study seeks to understand the historical trajectory of Higher Education Policy in Brazil since its inception. Logo has the conformation of conditionalities in the historical building of the National Policy of Student Assistance, configuration and operation in the institutions of Rio Grande do Sul, conducting an analysis of the concepts that are presented. From the data obtained from the research it was found that the conditionalities were being built to the right of the historical with retributive character, being created and recreated in the laws and ways of operation; his views are guided in a market logic and neoliberal meritocratic, individualistic, exclusive of retributive law, subject debtors and denial of rights, being able to conclude that the conditionalities perpetuate inequality and exclusion, stigma, subjecting individuals to a borrower's character, constituting themselves as a form of social exclusion and denial of rights.